Apoptotic effect of berberine via Bcl‐2, ROR1, and mir‐21 in patients with B‐chronic lymphocytic leukemia. (10th November 2020) - Mohammadlou, Maryam; Abdollahi, Maryam; Hemati, Maral; Baharlou, Rasoul; Doulabi, Ehsan Manouchehri; Pashaei, Mehrnoosh; Ghahremanfard, Farahnaz; Faranoush, Mohammad; Kokhaei, Parviz
Abstract : Berberine is a natural isoquinoline alkaloid that has been shown to inhibit the proliferation and induce apoptosis in a wide variety of tumor cells. However, the action mechanism of berberine in CLL cells is unknown. The previous study has shown that berberine leads to reduced viability and elevated levels of apoptosis in PBMCs of CLL patients. CLL cells are characterized by remarkable expression of Bcl‐2 and ROR1 which leads to activation and survival and increases disease progression in patients. High‐level expression of miR‐21 in patients with CLL is associated with a higher risk of death. Here we investigated the anticancer effects of berberine upon peripheral blood mononuclear cells (PBMCs) of CLL patients. To evaluate the expression of anti‐apoptotic proteins and ROR1 using flow cytometry and western blot, PBMCs were treated with 25 μM of berberine for 24 hr. The expression levels of mir‐21 were evaluated by real‐time PCR. Examination of treated cells demonstrated that berberine decreased Bcl‐2 and ROR1 levels. Although western blot results did not show any change in Bax as a pro‐apoptotic protein, an increased Bax/Bcl‐2 ratio indicated that mitochondrial pathway is involved in berberine‐induced apoptosis of CLL cells. Interestingly, berberine could reduce the expression of miR‐21 in comparison to the untreated group. Our findings describe some of the molecular mechanisms of berberine by decreasing Bcl‐2, ROR1, and mir‐21 which may be considered as a novel apoptosis inducer in CLL cells.